2020
DOI: 10.1002/cctc.202000674
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodebromination of Aromatic Bromides Catalyzed by Unsupported Nanoporous Gold: Heterolytic Cleavage of Hydrogen Molecule

Abstract: Unsupported nanoporous gold (AuNPore) is a highly efficient, practically applicable, and recyclable catalyst for hydrodebromination of aromatic bromides. The AuNPore-catalyzed hydrodebromination of aromatic bromides proceeded smoothly at relatively low hydrogen pressure and temperature to achieve good to excellent yields of the corresponding non-bromine variants. The selective hydrodebromination reaction occurred exclusively in the coexistence of chlorine atom. For the first time, a mechanistic study revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, all of these reactions are most likely more complex than merely involving a H 2 dissociation. The hydrodebromination, for instance, was performed in MeOH, and a substantial, quite similar turnover was detected even in the absence of H 2 . It is also notable that there was no reaction when no base was added, making it very likely that MeOH is being oxidized to formaldehyde, thus MeOH is the reductant.…”
Section: Catalysis By Nanoporous Gold In Organic Synthesismentioning
confidence: 96%
See 3 more Smart Citations
“…However, all of these reactions are most likely more complex than merely involving a H 2 dissociation. The hydrodebromination, for instance, was performed in MeOH, and a substantial, quite similar turnover was detected even in the absence of H 2 . It is also notable that there was no reaction when no base was added, making it very likely that MeOH is being oxidized to formaldehyde, thus MeOH is the reductant.…”
Section: Catalysis By Nanoporous Gold In Organic Synthesismentioning
confidence: 96%
“…It is also notable that there was no reaction when no base was added, making it very likely that MeOH is being oxidized to formaldehyde, thus MeOH is the reductant. Moreover, the reaction is not very tolerant of other functional groups: aldehydes, carbamates, and nitro groups get reduced and esters hydrolyze . In the other cases, it is not clear whether the solvent diethylamine was entirely innocent or, indeed, why triethylamine was used in the optimization reactions, whereas diethylamine was used in reactions in which the scope was explored .…”
Section: Catalysis By Nanoporous Gold In Organic Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…and Huang et al ., who demonstrated that Pt-based intermetallic nanoparticles have excellent catalytic selectivity, we prepared and used an unsupported nanoporous Pt–Fe bimetallic catalyst (PtFeNPore) for the chemoselective hydrogenation of HNBs. This study is based on our previous works for developing novel types of heterogeneous catalysts . The hydrogenation proceeded successfully, affording desired HANs in good to excellent yields with excellent selectivity when PtFeNPore was used as the catalyst (Scheme ).…”
Section: Introductionmentioning
confidence: 99%